2017
DOI: 10.3991/ijet.v12i10.7258
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors Affecting the Web-based Training Acceptance by Health Students, Applying UTAUT Model

Abstract: Nowadays Web-based training (WBT) is the most advanced training methods. With the increasing use of modern methods of training in universities necessity of identification of the factors influencing the acceptance of web-based training becomes more obvious. This study examines the factors influencing the acceptance of web-based training by students. This study was cross-sectional survey and conducted from August to December 2016. As sample, 239 students of Tabriz University of Medical Sciences (TUOMS) were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 0 publications
17
36
1
Order By: Relevance
“…SI had a significant and positive effect on students' behavioral intention to use BL. This part of the findings was consistent with other studies (17,28,33,38). Similarly, Ain et al (2016) reported that SI has positive effect on use of learning management system (44).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SI had a significant and positive effect on students' behavioral intention to use BL. This part of the findings was consistent with other studies (17,28,33,38). Similarly, Ain et al (2016) reported that SI has positive effect on use of learning management system (44).…”
Section: Discussionsupporting
confidence: 91%
“…FC expresses "the learner's insights into the existence of technological and organizational infrastructure and equipment to support the use of a system" (32). In this regard, Sattari et al (2017) showed that FC had a significant effect on behavioral intention and the use of the e-learning system (33). However, Hoque and Sorwar (2017) reported that FC had no significant effect on intention to use mobile health technology (28).…”
Section: Facilitating Condition (Fc)mentioning
confidence: 99%
“…FC expresses “the learner’s insights into the existence of technological and organizational infrastructure and equipment to support the use of a system” [ 33 ]. In this regard, Sattari et al (2017) showed that FC had a significant effect on the behavioral intention and use of e-learning system [ 34 ]. However, Hoque and Sorwar (2017) reported that FC had no significant effect on the users’ behavioral intention to use the mobile health service [ 29 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A developed questionnaire based on literature was used as the method of data collection [17][18][19][20][21] . The face validity of the questionnaire was approved by 10 professors of Tabriz University of Medical Sciences and reliability analysis showed Cronbach's of α= 0.7 proving the reliability of data collection instrument.…”
Section: Methodsmentioning
confidence: 99%